Investigation of phytochemical and biochemical attributes of hypoglycemic activity of Atriplex crassifolia (C.A. Mey) extracts in alloxan diabetic animal model - Sarah Rehman; Saiqa Ishtiaq; Sairah Hafeez Kamran; Muhammad Khalil-ur-Rehman; Syeda Farheen Fatima; Numera Arshad; Saira Rehman (PLoS ONE, 2025)
Diabetes mellitus is a widespread medical and public health issue that can lead to significant health impairment. The objective of the study was to assess the antidiabetic effectiveness of various extracts of Atriplex crassifolia (A. crassifolia), namely n-hexane (ACNH), dichloromethane (ACDCM), ethyl acetate (ACEA), and n-butanol (ACNB). The initial qualitative analysis revealed the presence of bioactive components in all extracts, such as alkaloids, glycosides, phenols, flavonoids, terpenes, and saponins. ACEA and ACNB exhibited considerable radical scavenging activity at different doses, as determined by the DPPH free radical scavenging experiment used to assess in-vitro antioxidant activity. Male rats were administered 150 mg/kg of alloxan monohydrate to develop diabetes. A preliminary investigation was conducted to evaluate the potential of all extracts to lower blood glucose levels using an oral glucose tolerance test (OGTT) at three different doses (250, 500, and 1000 mg/kg/day). ACEA and ACNB exhibited promising results in the OGTT, thus prompting a 28-day hypoglycemic research to confirm their biological effectiveness in treating diabetes. When taken orally, ACEA at doses of 500 and 1000 mg/kg/day, and ACNB at doses of 250, 500, and 1000 mg/kg/day, effectively recovered the concentrations of urea, creatinine, glucose, cholesterol, triglycerides, HDL, and liver enzymes (AST, ALT, and ALP). The histopathological evidence corroborated the conclusions. HPLC and GC-MS were employed to identify the presence of medically important phytoconstituents in ACEA and ACNB. Myrecitin and Quercitin were found using High Performance Liquid Chromatography (HPLC) in ACEA, while sinapic acid was identified in ACNB. The GC-MS analyses of ACEA and ACNB revealed the presence of several compounds with hypolipidemic, antioxidant, and anti-diabetic properties. The present study suggests that A. crassifolia has potential as a natural remedy for managing hyperglycemia, diabetic hyperlipidemia, and other diabetes-related problems.